Kānkhūapkhum panhā ʻǣnkō̜hō̜n dūai kotmāi : ʻēkkasān wichākān prakō̜p kānphitčhāranā phrarātchabanyat khūapkhum khrư̄angdư̄m ʻǣnkō̜hō̜n - Bandit Sō̜nphaisān; Čhuthāphō̜n Kǣomungkhun (Sūn Wičhai Panhā Surā, 2007)
Papers on the control of alcohol-related problems by implementing law and regulation.